SPHINGOSINE-1-PHOSPHATE AS A BIOMARKER AND PREDICTOR OF THE DEVELOPMENT OF SEVERE ACUTE RESPIRATORY SYNDROME IN PATIENTS WITH COVID-19 AND COMMUNITY-ACQUIRED PNEUMONIA - Komarevtseva, I.O.; Ihnatova, A.Yu.; Rudenko, I.V.; Kalinin, I.V.; Zhurba, O.A.; Balabanova, K.V.; Komarevtsev, V.N. (World of Medicine and Biology, 2023)
Sphingosine has been shown to prevent and eliminate bacterial infections of the respiratory tract, but it is unknown whether sphingosine can be also employed to prevent viral infections. The involvement in lung injury and endothelial barrier function, sphingosine-1-phosphate could be a potential biomarker of community-acquired pneumonia and COVID-19. The purpose of the study was to determine the diagnostic and prognostic value of sphingosine-1-phosphate and to unravel the complex role of sphingosine-1-phosphate in the pathophysiological pathways of community-acquired pneumonia and COVID-19 in conditions of hyperglycemia. Survival analysis (the advent of severe acute respiratory syndrome within 30 days of hospitalization) was performed using the Kaplan–Meier method; univariate analys were undertaken using log rank test and Cox’s regression model, respectively. Sphingosine-1-phosphate levels were approximately 2–2.5 times lower in women and men with pneumonia associated with hyperglycemia, Type 2 Diabetes and COVID-19. Moreover, this decrease was greater in men than in women. Sphingosine-1-phosphate is a biomarker of development of severe acute respiratory syndrome within 30 days of hospitalization in patients with COVID-19, community-acquired pneumonia (with and without hyperglycemia and Type 2 Diabetes).